P25 Short- and long-term mortality of subarachnoid hemorrhage according to hospital volume and severity using a nationwide multicenter stroke registry. (29th August 2022) - Oh, JS
Abstract : Introduction: Recent improvements in treatments for subarachnoid hemorrhage (SAH) have decreased mortality rates; however, the outcomes of SAH management are dependent on many other factors. In this study, we used nationwide, large-scale, observational data to investigate short- and long-term mortality rates after SAH treatment and the influence of patient severity and hospital volume. Patients and methods: We selected patients with SAH treated with clipping and coiling from the Korean Acute Stroke Assessment Registry. High- and low-volume hospitals were defined as hospitals that perform >20clipping and coiling procedures and ≤20 clipping and coiling procedures per year, respectively.Short- and long-term mortality were tracked using data from the Health Insurance Review and Assessment Service. Results: Among 2, 634 patients treated using clipping and coiling, 1, 544 (58.6%) and 1, 090 (41.4%) were hospitalized in high- and low-volume hospitals, respectively, and 910 (34.5%) and 1, 724 (65.5%) were treated with clipping and coiling, respectively. Mortality rates were 13.5%, 14.4%, 15.2%, and 16.1% at 3 months and 1, 2, and 4 years, respectively. High-volume hospitals had a significantly lower 3-month mortality rate. Patients with mild clinical status had a significantly lower 3-month mortality rate in high-volume hospitals than in low-volume hospitals. Patients with severe clinical status had significantly lower 1- and 2-year mortality rates in high-volume hospitals than in low-volume hospitals. Conclusion: Short- and long-term mortality in patients with SAH differed according to hospital volume. In the modern endovascular era, clipping and coiling can lead to better outcomes in facilities with high stroke-care capabilities. References: Pobereskin LH. Incidence and outcome of subarachnoid haemorrhage: a retrospective population based study. J Neurol Neurosurg Psychiatry 2001;70:340–3. DOI:10.1136/JNNP.70.3.340. Lee JY, Heo NH, Lee MR, Ahn JM, Oh HJ, Shim JJ, et al . Short and long-term outcomes of subarachnoid hemorrhage treatment according to hospital volume in korea: a nationwide multicenter registry. J Korean Med Sci 2021;36:E146. DOI:10.3346/JKMS.2021.36.E146. Do you have any conflict of interest to declare? : No